Systematic Analysis of the Translation of Cultural Elements in English and French Versions of Mofolo’s Moeti oa Bochabela - Seutla, Lieketso Agatha (International Journal of Linguistics and Translation Studies, 2024)
This study analyses the translation of cultural elements in the two translations of Thomas Mofolo’s Moeti oa Bochabela. The research objectives sought to identify the cultural elements in the two translations, the techniques and strategies used in rendering them, bring out the discrepancies in translating cultural elements in the two translations and suggest improvements for inadequate translations. Data was collected from the three novels and other documents after which a comparative analysis was done. The current study was guided by Descriptive Translation Studies (DTS), Philological theories of translation, Skopos Theory, Manipulation Theory and Socio-Linguistic Theory. Its findings reveal that the techniques that were used to render cultural elements in the corpus under study include literal translation, borrowing and calque, which are source text-oriented, and cultural equivalence, explicitation, reformulation, expansion, description, transposition, adaptation and omission, which are target text-oriented. The two categories of techniques fall under foreignization and domestication strategies respectively. The study also shows that in both translations, the cultural elements were more domesticated than foreignized. The English translation has more foreignization than the French one while the French translation has more domestication than the English version. Although not in all cases, there are discrepancies in the rendering of cultural elements in the two translations.